Implementation Evaluation of Occupational Health and Safety Management System (SMK3) Based on Government Regulation No. 50 of 2012 at PT Integrasi Aviasi Solusi - Nela, Dinda Da; Pramadita, Suci; Sulastri, Aini (Jurnal Teknik Sipil, 2025)
PT Integrasi Aviasi Solusi is a service provider in the aviation industry covering ground handling, cargo, logistics, and operational support. Activities in the cargo segment involve a significant level of hazard risk, thereby requiring the implementation of an Occupational Health and Safety Management System (SMK3) in accordance with regulations. This study aims to evaluate the hazard risk levels at the Pontianak Branch Office, assess the implementation level of SMK3 in accordance with Government Regulation No. 50 of 2012, and provide recommendations for improving risk control strategies. The Research data were obtained through field observations, interviews, documentation, and the use of OHSMS checklists. Risk analysis was conducted using the Job Safety Analysis (JSA) method and the AS/NZS 4360:2004 standard, while the evaluation of OHSMS implementation employed a regulatory compliance instrument. The results identified 54 potential hazards, consisting of 34 low-risk and 20 medium-risk hazards. The evaluation of OHSMS implementation showed a compliance level of 97%, with 62 criteria fulfilled and two criteria unmet (3%). These findings indicate that the implementation of OHSMS in the cargo unit has been carried out effectively; however, improvements in certain aspects are still required to strengthen the effectiveness of risk control.